MENELAAH TUJUAN PENDIDIKAN INDONESIA DARI PERSPEKTIF FILSAFAT BARAT DAN ISLAM:STUDY KOMPARATIF PEMIKIRAN PLATO DAN AL-GHAZALI - Wulan Octi Pratiwi; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
The success of the learning and learning process in education, one of which depends on the clarity of goals. The purpose of national education leads to the formation of four aspects, namely, the religious aspect, the moral aspect, the intellectual aspect, and the national aspect. All these aspects are realized in order to form a complete and complete human being. This study describes the concept of Indonesian education goals from the perspective of western and Islamic philosophy according to Plato and Al-Ghazali's thoughts in depth, comparing the two educational thoughts with the goals of Indonesian education. The research method used in this study is the Literature Review method. The approach in the research is a comparative study with the object of discussion focused on the thoughts of the two figures about the concept of education. The results of this study state that the goals of national education in Indonesia are very relevant to the concept of educational goals according to Plato and Al-Ghazali because the two concepts of thought from western and Islamic philosophers place great emphasis on aspects of intellectual, moral, and spiritual development of students referring to the values ​​of the value of humanity, immortality and divinity